Acute lymphoblastic leukemia: A population‐based study of outcome in the United States based on the surveillance, epidemiology, and end results (SEER) database, 1980–2017. Issue 6 (1st April 2021) - Sasaki, Koji; Jabbour, Elias; Short, Nicholas J.; Jain, Nitin; Ravandi, Farhad; Pui, Ching‐Hon; Kantarjian, Hagop
Abstract: The treatment in acute lymphoblastic Leukemia (ALL) has evolved and improved dramatically over the past four decades. We assessed the outcome of ALL overall, and the two major subsets of Philadelphia chromosome (Ph)‐positive and Ph‐negative ALL by age, time periods, ethnicity, median household income, and geographic county area. A total of 12 788 patients diagnosed with ALL from 1980 to 2017 were included. We performed an analysis to better evaluate the outcome evolution in ALL according to time period and patient's demographic factors. The overall 5‐year survival rates have improved significantly over time, from 51% before 1990 to 72% since 2010. The survival rates for children (age 0 to 14 years) and adolescents (age 15 to 19 years) have improved from 73% and 55% before 1990 to 93% and 74% since 2010, respectively. Similarly, the rates had improved from 33% to 59% for adults 20 to 29 years old, 24% to 59% for 30 to 39 years old, and 14% to 43% for 40 to 59 years old between the two time periods. The rates remained under 30% in older patients (60+ years). Since 2010, patients with Ph‐negative ALL had 5‐year survival rate of 73% and those with Ph‐positive ALL 50%. African Americans, Hispanic ethnicity, and lower household income were associated with inferior survival. The outcome of patients with ALL showed continued improvement across all age groups in the US. The recent introduction of targeted therapies, together with optimized supportive care, will continue to improve outcomes, particularly in older patients.